Multi-strategy ensemble artificial bee colony algorithm for large-scale production scheduling problem. (2015) - Wang, Hui; Wang, Wenjun; Sun, Hui
This paper presents a multi-strategy ensemble artificial bee colony (MEABC) algorithm for solving large-scale production scheduling problem. MEABC is a new variant of artificial bee colony (ABC), which has shown good performance on many continuous optimisation problems. To apply MEABC to discrete production scheduling problem, the smallest position value (SPV) rule is employed. Moreover, a modified NEH-based population initialisation method is utilised for generating high-quality initial solutions. Experimental study is conducted on a set of 140 flow shop scheduling problems with the size from 20 × 5 to 2, 000 × 100. Simulation results show that MEABC performs better than the NEH and ABC on all test instances.